2005
DOI: 10.1128/iai.73.3.1797-1810.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genome-Wide Expression Profiling and Mutagenesis To Study the Intestinal Lifestyle of Campylobacter jejuni

Abstract: Campylobacter jejuni is the most common bacterial cause of diarrhea worldwide. To colonize the gut and cause infection, C. jejuni must successfully compete with endogenous microbes for nutrients, resist host defenses, persist in the intestine, and ultimately infect the host. These challenges require the expression of a battery of colonization and virulence determinants. In this study, the intestinal lifestyle of C. jejuni was studied using whole-genome microarray, mutagenesis, and a rabbit ileal loop model. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
123
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 57 publications
9
123
1
Order By: Relevance
“…2 and 3). This regulatory feature is similar to that of CmeABC (21,22) and is consistent with the findings of other investigators that Cj0561c and cmeABC are upregulated in the intestinal tract (40,47), where bile compounds are present. Although CmeR is the primary factor controlling the expression of Cj0561c, the transcription of Cj0561c was further induced by bile salts in the CmeR-negative background (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…2 and 3). This regulatory feature is similar to that of CmeABC (21,22) and is consistent with the findings of other investigators that Cj0561c and cmeABC are upregulated in the intestinal tract (40,47), where bile compounds are present. Although CmeR is the primary factor controlling the expression of Cj0561c, the transcription of Cj0561c was further induced by bile salts in the CmeR-negative background (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequent tests using realtime qRT-PCR confirmed that cmeA (10-fold) and cmeC (15-fold) were also upregulated in 11168⌬cmeR. The lack of simultaneous detection of all genes in an affected operon by the DNA microarray has also been observed in other studies (40,47) and suggests that DNA microarray analysis has a lower sensitivity than real-time qRT-PCR. Interestingly, Cj0583 showed a 6.6-fold change in expression when the DNA microarray was used, but this was not verified by real-time RT-PCR (Table 3).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A connection between negative regulation of the HSR and positive regulation of motility-associated genes has also been described for Helicobacter pylori (Roncarati et al, 2007). Stintzi et al (2005) have reported the analysis of an hrcA mutant and shown that this gene may also have a role in virulence. Despite this, the regulon of HrcA in C. jejuni has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that MazG has a role in cellular 'house-cleaning' by removing abnormal (d)NTP's from nascent DNA strands (Galperin et al, 2006), in addition to regulating programmed cell death in E. coli (Gross et al, 2006). It also regulates intracellular levels of (p)ppGpp, the main nutritional stress signal molecule involved in the stringent response, which has been shown to be an important response in Campylobacter jejuni during intestinal colonization (Stintzi et al, 2005). By reducing (p)ppGpp levels, MazG has a central role in maintaining cell viability during nutritional stress, which could be important in the gut during periods of intermittent availability of certain nutrients, whereas (p)ppGpp itself is required for growth during osmotic stress in L. monocytogenes (Okada et al, 2002).…”
Section: Discussionmentioning
confidence: 99%